Assessing the social climate of physical (in)activity in Canada - Yun, Lira; Vanderloo, Leigh; Berry, Tanya R; Latimer-Cheung, Amy E; O’Reilly, Norman; Rhodes, Ryan E; Spence, John C; Tremblay, Mark S; Faulkner, Guy (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Ecological models suggest that a strategy for increasing physical activity participation within a population is to reconstruct the “social climate”. This can be accomplished through 1) changing norms and beliefs, 2) providing direct support for modifying environments, and 3) implementing policies to encourage physical activity. Nevertheless, surveillance efforts have paid limited attention to empirical assessment of social climate. This study responds to this gap by assessing the social climate of physical activity in Canada. Methods A representative sample of Canadian adults (n = 2519, male/female = 50.3%/49.7%, Mage = 49.1 ± 16.3 years) completed an online survey asking them to assess social climate dimensions including social norms of physical (in)activity, perceptions of who causes physical inactivity and who is responsible for solving physical inactivity, and support for physical activity-related policy. Descriptive statistics (frequencies) were calculated. Multinomial logistic regressions were constructed to identify whether demographic variables and physical activity participation associated with social climate dimensions. Results Physical inactivity was considered a serious public health concern by 55% of the respondents; similar to unhealthy diets (58%) and tobacco use (57%). Thirty-nine percent of the respondents reported that they often see other people exercising. Twenty-eight percent of the sample believed that society disapproves of physical inactivity. The majority of respondents (63%) viewed the cause of physical inactivity as both an individual responsibility and other factors beyond an individuals’ control. Sixty-seven percent of respondents reported physical inactivity as being both a private matter and a public health matter. Strong support existed for environmental-, individual-, and economic-level policies but much less for legislative approaches. The social climate indicators were associated with respondents’ level of physical activity participation and demographic variables in expected directions. Conclusion This study is the first known attempt to assess social climate at a national level, addressing an important gap in knowledge related to advocating for, and implementing population-level physical activity interventions. Future tracking will be needed to identify any temporal (in)stability of these constructs over time and to explore the relationship between physical activity participation and indicators of the national social climate of physical activity.